RELATIONSHIP BETWEEN FAMILY ENVIRONMENT AND STUDENT LEARNING ACHIEVEMENT - Rismalaini (IICLS (Indonesian Institute for Corporate Learning and Studies), 2025)
This study aims to investigate the relationship between family environment and student achievement in secondary schools. Family environment, which includes emotional support, communication, and parental involvement in education, is believed to have a significant influence on students' academic development. The method used in this study was a survey with a sample of 200 students from various socio-economic backgrounds. Data were collected through a questionnaire that measured aspects of the family environment and student achievement as measured by report card scores. The results of the analysis showed that there was a significant positive relationship between family environment and student achievement. Students who come from a supportive family environment, with good communication and high parental involvement, tend to have better learning achievement compared to students who come from a less supportive family environment. This finding indicates the importance of the role of the family in the educational process and encourages parents to be actively involved in their children's education. This study concludes that a positive family environment can contribute significantly to student achievement, so it is expected to be a consideration for educators and policy makers in designing interventions that involve parents in children's education.